Perancangan Website Profil Kampus Amikom Jurusan D3 Komputerisasi Akuntansi - Muhammad Dima Alfarizi; Ina Sholihah Widiati; Muhammad Setiyawan (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
They provide information services that use the hyperlink concept, which can facilitate Internet users' search for information on the Internet. A company profile website can store more interesting data of pictures, sounds, animation, text, table, diagram and other data shapes. The website forms the entire web page in a domain that contains the information of a corporation. Amikom surakarta's accounting computerization still does not provide information media as it does on other colleges that use information technology, with a company profile website, d3 a computerized accounting for amikom surakarta has medium to expand information media.